Policing in Israel: studying crime control, community policing, and counterterrorism - Jonathan-Zamir, Tal; Weisburd, David; Ḥasisi, Badi (Advances in police theory and practice series, 2016)
Policing in Israel : Studying Crime Control, Community, and Counterterrorism : Editors' Introduction / Tal Jonathan-Zamir, David Weisburd, and Badi Hasisi -- Law of Concentrations of Crime at Place : Case of Tel Aviv-Jaffa / David Weisburd and Shai Amram -- Vehicle Impoundment Regulations as a Means of Reducing Traffic Violations and Road Accidents in Israel / Tova Rosenbloom and Ehud Eldror -- Lean Management for Traffic Police Enforcement Planning / Nicole Adler, Jonathan Kornbluth, Mali Sher, and Shalom Hakkert -- Organizational Structure, Police Activity, and Crime / Itai Ater, Yehonatan Givati, and Oren Rigbi -- Police, Politics, and Culture in a Deeply Divided Society / Badi Hasisi -- Crime Victims and Attitudes toward Police : Israeli Case / Gali Aviv -- Procedural Justice, Minorities, and Religiosity / Roni Factor, Juan Castilo, and Arye Rattner -- Police Understanding of Foundations of Their Legitimacy in the Eyes of the Public : Case of Commanding Officers in Israel National Police / Tal Jonathan-Zamir and Amikam Harpaz -- Terrorist Threats and Police Performance : A Study of Israeli Communities / David Weisburd, Badi Hasisi, Tal Jonathan-Zamir, and Gali Aviv -- Police Legitimacy under the Spotlight : Media Coverage of Police Performance in the Face of High Terrorism Threat / Revital Sela-Shayovitz -- Policing Terrorism and Police-Community Relations : Views of Arab Minority in Israel / Badi Hasisi and David Weisburd -- How Has Israel National Police Perceived Its Role in Counterterrorism and Potential Outcomes? : A Qualitative Analysis of Annual Police Reports / Tal Jonathan-Zamir and Gali Aviv -- Lessons from Empirical Research on Policing in Israel : Policing Terrorism and Police-Community Relationships / Simon Perry and Tal Jonathan-Zamir